AUGMENTING ISLAMIC DIGITAL PAYMENT EFFECT ON MUSLIM CUSTOMER PURCHASE DECISION ON MICRO, SMALL AND MEDIUM ENTERPRISES’ (MSMEs) PRODUCTS - Riofita, Hendra (Bank Indonesia, 2024)
To support the role of digital transaction in improving the growth of economy, the effect of Islamic digital payments on Muslim customer purchase decision on Micro, Small and Medium Enterprises’ (MSMEs) products should be augmented. This study employs a modified Technology acceptance Model (TAM) to examine whether perceived values mediate or augment the effect of Islamic digital payments on purchase decisions of MSMEs’ products. Using data gathered from 477 respondents, we find that the perceived values do augment Islamic digital payment effect on Muslim customer purchase decision on MSMEs products. However, their augmentation for the case of cash payments is absent. In other words, Islamic digital payments and perceived values are together the predictors of Muslim customer purchase decision while cash payments are not. We also note that the Islamic digital payments are the predictor of perceived values.